ANALISIS KOMPETENSI ABSOLUT BAGI PERMASALAHAN UMAT ISLAM DI PENGADILAN AGAMA - Lubis, Fauziah; Rangkuti, Shindy Tamanda; Harahap, Muthia Sartika; Aziz, Muhammad; Hasibuan, Nurul Hakiki; Hidayah, Khairul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The purpose of this study is to analyze in depth the legal basis and limits of the absolute authority of the Religious Court in resolving various legal issues of Muslims in Indonesia, and to identify the legal implications of the misapplication of this authority. The issues raised focus on the importance of properly understanding absolute and relative competence in civil procedural law, especially to avoid errors in determining the competent court forum. Through a normative legal approach and literature study, this study explores the scope of the absolute authority of the Religious Court over cases such as marriage, inheritance, wills, grants, waqf, zakat, infaq, shadaqah, and sharia economics as regulated in Law Number 3 of 2006 and other related laws and regulations. The results of the analysis show that absolute competence plays an important role in maintaining judicial order, preventing overlapping jurisdictions, and ensuring legal certainty and justice for the Muslim community in Indonesia.